(3ef GdMOGKI Gdi GdYhdeIs (3QDi hhLgGJ fXQ ai bVjI GdJWhjQ h GdJZjjQ GdGLJeGYis - (3QhHjQJS, L(B.(3JjehfRs ((3GdchjJs (3GdeLdS GdhWfi ddKbGaI h Gdafhf h GdBOGHs, 2004)
(3jJMOK GdcJGH Yf GdJZjQ GdGLJeGYi ddOhd GdfGejI hcjajI eSGYOJgG MJi JUjQ CcKQ MOGKI ef NdGd hLgGJ fXQ eNJdaI ddJfejI h GdYhdeI h GdJWhQs
4 6 18
Keywords: (3GdJWhQ GdGLJeGYis; (3GdJZjjQ GdGLJeGYis; (3GdYhdeIs